Ethnic heterogeneity in the Malaysian economy: a special reference to the ethnic group participation in financial planning activities - Shafii, Zurina; Zainal Abiddin, Norhasni; Ahmad, Abdul Razaq (The Journal of International Social Research, 2009)
The purpose of this article is to outline the current state of knowledge in relation of economic involvement and ethnicity in Malaysia. Firstly, this article will review on the state of employment in relation to the ethnic groups in Malaysia. This is important since the income factor is one of the major factors that determine the level of economic participation and the state of wealth of individuals. Stable and adequate level of income is one of the determinants of wealth accumulation for individuals other than wealth and net wealth level. This raises the question of employment opportunities among different ethnic groups in Malaysia. The root of the employment opportunities, it can be argued, stems from the access of different ethnic groups to high education, which also be discussed in the article. Secondly, this article will review on the involvement of various ethnic groups in Malaysia in several financial planning sector including investment and risk management sector. At the end of the article, it will provide insights on the current state of financial planning activities which reflect the participation of the individuals with different ethnic plan their financial affairs.